Hybrid Logarithmic Percentage Change-Driven Objective Weighting and MOORA in Salesperson Performance Assessment - Gufran Umar, M. Kasyif; Abdurahman, Muhdar; Wahyudi, Agung Deni; Octaviansyah Pasaribu, A. Ferico (STMIK Budi Darma, 2024)
A salesperson is an individual who is responsible for selling a company's products or services to customers, either directly or through various marketing channels. The main problem in determining the best salesperson is often related to the complexity of assessing various aspects of performance comprehensively and fairly. While metrics such as sales volume are easy to measure, other important aspects such as the ability to build long-term relationships with customers, customer satisfaction, and contribution to team dynamics are more difficult to measure objectively. The purpose of this study was to combine LOPCOW and MOORA in the performance appraisal of salespeople. This study aims to address several challenges associated with the assessment of sales force performance, including heteroscedasticity in sales data and complexity in evaluating relevant multi-criteria criteria. By integrating LOPCOW to manage heteroscedasticity in sales data and MOORA to consider various aspects of sales force performance, resulting in a weighting method that can provide more accurate and comprehensive performance appraisals. The results of the salesperson performance ranking the 1st rank with the final value of MOORA 0.35861 with the name Salesperson HS, the 2nd rank with the final value of MOORA 0.34241 with the name Salesperson FT, and the 3rd rank with the final value of MOORA 0.3347 with the name Salesperson TS.